Incorporation of Rice Husk Ash for the Improvement of Mechanical Properties of Clay Soils for the Paving of the Santa Rosa de Combayo Highway, Cajamarca (LACCEI, 2024)
The present investigation has as a general objective to determine the influence of the addition of rice husk ash on the mechanical properties of clayey soils for paving the Santa Rosa de Combayo highway. Regarding the methodology, a quantitative approach with an experimental design is considered, which has a population of 10 km that make up the Santa Rosa de Combayo Highway and as a study sample, a pit is analyzed in relation to a 1 km section in the area of study. The results of the C-01 soil sample, both for the one corresponding to the natural state and for those added, are a CL soil classification by SUCS and A-7-6 (12) by AASHTO. The standard clayey soil sample obtained a CBR at 95% of the Maximum Dry Density, a value of 16.40% and with the addition of 7.5% and 8.5% rice husk ash, it was possible to obtain CBR values of 36% and 34 % respectively. Finally, it is concluded that the optimal percentage of incorporation of rice husk ash is 7.5% in clayey soils of the Santa Rosa de Combayo highway, Cajamarca.